(Patience) in the linguistic heritage and religious study of gramophone - Al-’Ani, Ibtisam Th. M. (Humanities Journal of University of Zakho, 2014)
Patience of the attributes of the prophets and the righteous and faithful, has been received much patience in the Quranic stories and sayings of the Prophet the greatest (peace be upon him). Used the Koran the word patience in various formats and the significance of many collected in this research. Began to search for this word when linguists and owners of dictionaries. Came formats nominal and the other contained in the actual research in detail.The significance of many came, talked about the commentators and scholars, from the results of research that has a balance of patience and God Aigdr to bear only the grace of God overtook them patience; because of this blessing, pay and reward and high houses. Patience has great benefits for humans, including endurance and the ability to pass the trials